Importance of Video-EEG Monitoring in the Diagnosis of Refractory Panic Attacks. (24th July 2013) - Kirmani, Batool F.; Mungall, Diana
Abstract : Partial seizures can be misdiagnosed as panic attacks. There is considerable overlap of symptoms between temporal lobe seizures and panic attacks making the diagnosis extremely challenging. Temporal lobe seizures can present with intense fear and autonomic symptoms which are also seen in panic disorders. This results in delay in diagnosis and management. We report an interesting case of a young woman who was diagnosed with right temporal lobe seizures with symptoms suggestive of a panic attack.